Methane clumped isotopes: Progress and potential for a new isotopic tracer. (November 2017) - Douglas, Peter M.J.; Stolper, Daniel A.; Eiler, John M.; Sessions, Alex L.; Lawson, Michael; Shuai, Yanhua; Bishop, Andrew; Podlaha, Olaf G.; Ferreira, Alexandre A.; Santos Neto, Eugenio V.; Niemann, Martin; Steen, Arne S.; et al.
Highlights: We present a review and an expanded dataset of methane clumped isotope measurements. Methane clumped isotope values often indicate equilibrium formation temperature. Kinetic effects during or after methane production can affect clumped isotope values. The wide variability in clumped isotope values suggests it will be a useful tracer. Abstract: The isotopic composition of methane is of longstanding geochemical interest, with important implications for understanding petroleum systems, atmospheric greenhouse gas concentrations, the global carbon cycle, and life in extreme environments. Recent analytical developments focusing on multiply substituted isotopologues ('clumped isotopes') are opening a valuable new window into methane geochemistry. When methane forms in internal isotopic equilibrium, clumped isotopes can provide a direct record of formation temperature, making this property particularly valuable for identifying different methane origins. However, it has also become clear that in certain settings methane clumped isotope measurements record kinetic rather than equilibrium isotope effects. Here we present a substantially expanded dataset of methane clumped isotope analyses, and provide a synthesis of the current interpretive framework for this parameter. In general, clumped isotope measurements indicate plausible formation temperatures for abiotic, thermogenic, and microbial methane in many geological environments, which is encouraging for the further development of this measurement as a geothermometer, and as a tracer for the source of natural gas reservoirs and emissions. We also highlight, however, instances where clumped isotope derived temperatures are higher than expected, and discuss possible factors that could distort equilibrium formation temperature signals. In microbial methane from freshwater ecosystems, in particular, clumped isotope values appear to be controlled by kinetic effects, and may ultimately be useful to study methanogen metabolism.